Epidemiology of suspected life-threatening perioperative anaphylaxis: a cross-sectional multicentre study in China. (January 2022) - Zhang, Panpan; Liu, Xiaowen; Li, Weixia; Gong, Ruisong; Zuo, Jun; Sun, Ruihua; Zhao, Jing; Mandell, Mercedes S.
Abstract: Background: Perioperative anaphylaxis is relatively rare but can be life-threatening. The incidence in China is unknown and may differ from other global geographic regions. This study was therefore designed to understand the incidence of perioperative anaphylaxis in China. Methods: We enrolled 112 tertiary care hospitals from seven distinct geographic areas in mainland China. We collected information about Ring and Messmer III and IV reactions from September 2018 to August 2019. A collaborative educational learning network was used to reduce diagnostic errors. Information about patient characteristics, clinical features, treatment, and clinical outcomes were recorded and analysed. Results: A total of 447 cases of 5 078 118 surgical procedures met inclusion criteria. The incidence of suspected perioperative anaphylaxis throughout China was one in 11 360 anaesthetics (95% confidence interval [CI], with a range of 1:12 521 to 1:10 397). The incidence in South China was higher (one in 6050; 95% CI, from 1:8013 to 1:4859) than in Northeast China (one in 19 262; 95% CI, from 1:33 088 to 1:13 585) ( P <0.01) with an increasing trend from the north to the south. The most common clinical manifestations were hypotension (91.1%) and tachycardia (65.3%). The majority of patients (83.4%) were given epinephrine. A total of 27 patients (6.0%) required cardiopulmonary resuscitation. Ultimately, nine patients died (2.0%). Conclusions: This nationwide survey showed an incidence of perioperative anaphylaxis of one in 11 360, but this varied significantly by region. The underlying reason for this pattern remains unknown and could be attributable to environmental or genetic influences, which requires further investigation. Clinical registry number: ChiCTR1900025956.